Gaya Bahasa Sindiran dalam Komunikasi Digital: Analisis Retoris dan Pragmatik terhadap Unggahan Media Sosial Gibran Rakabuming Raka - Ebe, Andi; Nurfaizah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Abstract: This study investigates the use of satirical language in the digital communication of Gibran Rakabuming Raka on the social media platform X (Twitter). Employing a descriptive qualitative approach, the analysis applies Gorys Keraf’s typology of satirical styles in conjunction with Paul Grice’s Cooperative Principle. The findings indicate that Gibran strategically employs irony, cynicism, sarcasm, and satire as rhetorical devices to respond to criticism, articulate political views, and construct his public persona. Pragmatic analysis reveals frequent flouting of Grice’s maxims, thereby generating implicatures that enhance communicative effectiveness. The study underscores that satire, beyond its perceived negative connotation, functions as a deliberate communicative strategy that reflects the pragmatic and rhetorical competence of a public figure.